ANALISA PROYEK SISTEM INFORMASI VEHICLE SECURITY MENGGUNAKAN METODE ANALISIS SWOT DAN TELOS - Risky Kurniawan, Risky Kurniawan (Prodi Sistem Informasi FST Universitas Jambi, 2022)
The aim of this research was to know the analysis results of the applications information system project based on the Internet of Things (IoT) Vehicle Security using SWOT analysis technical and TELOS feasibility test. The research was applying qualitative research with a descriptive approach. Based on the results of the study, the answer of the study showed that the results of the SWOT analysis is a positive although there are several things that need to be addressed in the future. Meanwhile, the results of the TELOS feasibility test show that the production results are 8.34 or if rounded to 8, which means that the information system project is very feasible to continue to be developed. The researcher concluded, that The Vehicle Security Information System project is considered to have fulfilled four factors in the SWOT Analysis Technique and is considered to have met the five factors of the TELOS Feasibility Test. The researcher suggests, that in terms of regulations and promotional media, it must be improved because even though it is still a new product, this vehicle security application has a great opportunity in Indonesia, which has very high vehicle theft criminal statistics.